Assessment of some high ratio propagation technologies for quality seed yam tuber production in Dioscorea alata L. and Dioscorea rotundata Poir - Pelemo, O.S. (University of Ibadan, 2021)
Edible yams are widely cultivated staple food crops in the tropics, but their production is constrained by low multiplication ratio, which results in short supply of Seed Yam Tubers (SYT). The use of High-ratio Propagation Technologies (HrPT) could enhance quality and quantity of SYT. However, limited information is available on the use of HrPT and the amenability of yam varieties to HrPT for SYT production. In this study, the uses of some HrPT for quality SYT production in Dioscorea alata and Dioscorea rotundata were investigated. Three HrPTs: Conventional Tissue Culture (CTC), Aeroponics System (AS) and field-based Yam Minisetts Technique (YMT) were evaluated for yam propagation using standard procedures. Five yam varieties (TDr9519177, TDr9518544, TDr8902665, TDa291 and TDa9801176) cultured in six growth media [4.43 g/L Murashige and Skoog (MS) basal medium and 7.0 g of agar-agar supplemented with each of 30 g/L sucrose-M1, 60 g/L sucrose-M2, 0.1mg/L Jasmonic Acid (JA)+30 g/L sucrose-M3, 0.1 mg/L JA+60 g/L sucrose-M4, 1mg/L-Naphthalene Acetic Acid (NAA)+30 g/L sucrose-M5 and 0.1 mg/L NAA+60 g/L sucrose-M6] using three light types [blue-Light Emitting Diode (LED), red-LED and white-LED] in CTC experiment were evaluated for Number of Nodes-NN, Number of Vines-NV and Vine Length-VL (cm). Explants from Acclimatised Tissue Cultured Plants-ATCP, Direct Vine Cuttings-DVC and Rooted Vine Cuttings-RVC of the five yam varieties were grown in AS and evaluated for Plant Survival-PS, Number of Tubers-NT and Fresh Tuber Weight-FTW (g). Using the YMT, four D. alata and 12 D. rotundata varieties were evaluated on the field using five Sett Weights-SW (10, 20, 30, 40 and 50 g). Data on Plant Emergence-PE (%), NT, SYT (%) and Fresh Tuber Yield-FTY (t/ha) were analysed using descriptive statistics and ANOVA at α 0.05. Across varieties, NN, NV and VL differed significantly among media and light types. The NN, NV and VL ranged from 3.3±0.9 (M6, red-LED) to 15.9±1.1 (M3, white-LED), 1.2±0.3 (M2, Blue-LED) to 3.2±0.8 (M4, white-LED) and 4.3±0.9 (M6, red-LED) to 10.5±1.0 (M6, red-LED), respectively. The PS, NT and FTW varied significantly among yam varieties and explant sources. The PS across varieties was in the order: ATCP (52.0±14.5)>DVC (35.4±11.6)>RVC (28.3±16.0). The NT ranged from 12.3±0.6 (TDa9801176, DVC) to no tuber (TDa291, RVC). The FTW obtained from ATCP, DVC and RVC ranged from 6.2±15.1 (TDa291) to 257.8±3.2 (TDr9518544), 0.0 (TDr8902665) to 157.0±3.5 (TDr9518544) and 0.0 (TDa291) to 147.8±3.3 (TDa9801176), respectively. Effects of variety, SW and variety×SW interaction in YMT were significant on PE, NT and FTY. Across SW, PE declined from 97.7±9.5 (TDa9801176) to 40.5±7.6 (Danacha). Across varieties, NT ranged from 13.1±1.3 (10 g SW) to 20.3±3.8 (50 g SW), while FTY ranged from 8.6±2.6 (10 g SW) to 20.7±4.3 (50 g SW). The proportion of SYT was highest (66.9±6.0) in 20 g SW and lowest (55.1±13.1) in 50 g SW. Jasmonic acid supplemented medium, white light emitting diode, tissue culture plants, sett weights of 20 g and varietal effect enhanced propagation and seed yam tuber production in Dioscorea alata and Dioscorea rotundata.